INTEGRATED PLANT NUTRITION APPROACHES FOR POTATO - Banafar, R. N. S.; Billore, M.; Kushwah, S. S. (Potato Journal, 2013)
A field experiment was conducted at Indore, Madhya Pradesh during 1996-97 with potato cultivar Kufri Jyoti. The growth parameters and yield of potato was significantly influenced by the organic manures and chemical fertilizers. Maximum plant height (43.56 cm), fresh weight of shoot per plant (361.40 g), dry weight of shoot per plant (23.73 g), leaf area per plant (77.68 cm2), tuber yield (265.27 qha-1) and dry matter content in tuber (22.58%) were recorded with the application of 100% recommended NPK + 15 t FYM followed by 75% NPK + 15 t poultry manure ha-1. The performance of 75% NPK + 15 t biogas slurry BGS and 75% NPK+ 15 t Nadep compost with regard to yield of tuber and dry matter content in tuber was identical to that of 100% NPK + 15 t FYM or 75% NPK + 15 t poultry manure. The highest net income as well as benefit: cost ratio (2.30) were obtained with the application of 100% NPK + 15 t FYM ha-1.